Psychology and Education - Jung, C. G. (Carl Gustav), 1875-1961 (Book collections on Project MUSE., 1969)
Extracted from The Development of the Personality, Vol. 17, Collected Works, Jung's early study "Psychic Conflicts in a Child'' (1910) with later papers on child development and education including "The Gifted Child" (1946). Originally published in 1969. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905